Low diacylglycerol values in colonic adenomas and colorectal cancer. Issue 9 (September 1990) - Sauter, G; Nerlich, A; Spengler, U; Kopp, R; Pfeiffer, A
Abstract : The biochemical events that make colonic epithelial cells proceed along the adenoma-carcinoma sequence are not well understood. The phosphoinositol signal transduction pathway is involved in the regulation of cell growth and differentiation. To determine its role in colonic neoplasias we performed mass measurements of its second messenger sn-1, 2-diacylglycerol in biopsy specimens from normal mucosa and neoplasias of the colon. Normal colonic mucosa was also investigated in patients without colonic abnormalities (n = 10). Compared with pooled diacylglycerol values from five colonic sites (100%), values in patients with a normal colon were highest in the ascending colon (120 (5)%, p less than 0.05) and lowest in the rectum (81 (5)%, p less than 0.01). Absolute diacylglycerol values in patients with normal colons (2.62 (0.16) nmol/mg protein) were not significantly different from those found in the normal mucosa of patients with colorectal neoplasias (2.45 (0.17) nmol/mg protein). Both colonic adenomas (n = 15) and colorectal carcinomas (n = 14) showed significantly decreased diacylglycerol values compared with the adjacent normal mucosa of each patient (72 (4)%, p less than 0.001, and 71 (4)%, p less than 0.001 respectively). The appreciable decrease in mass diacylglycerol values clearly distinguishes adenomas and carcinomas of the colon from the surrounding normal mucosa. This finding suggests that profound metabolic changes of the phosphoinositol signal transduction pathway occur early in the adenoma-carcinoma sequence and may be important in colonic carcinogenesis.